SPACE OF THE REGIONAL AGGLOMERATIONS AND RE-INDUSTRIALIZATION - Shubenkov, Mikhail Valerievich; Khomyakov, Dmitriy Alksandrovich (Journal of Applied Engineering Science, 2016)
The article is devoted to the analysis of the potential to fabricate production processes and their accompanying infrastructure networks as a part of urban areas. The authors explore the mechanisms of expelling production and services to outskirts by modern "post metropolises". The processes showing how industries return to big cities and overcome urban fabric, stating their areas as promising targets to outbound investments, have been analyzed for the first time. The survey findings have revealed the possible ways to increase self-sustainability of cities and reduce consumption of external resources as well as to increase their efficiency due to different factors including distributed energy generation and consumption systems.
Keywords: Urbanization; Regions; Products; processing; Infrastructure; INDUSTRIALIZATION; fabricators; consumption; city; Area; agglomerations